Clinical Use of Ketodex in Managing Dental Anxiety: A Systematic Review with Statistical Analysis Plan - Matos, Jefferson David Melo de; Andrade, Valdir Cabral; Morais, Tales Cyríaco; Porto, Marina Fonseca; Batista, Heitor Oliveira de; Queiroz, Daher Antonio; Ramos, Umberto Demoner; Batista, João Pedro Oliveira de (Brazilian Journal of Implantology and Health Sciences, 2025)
This literature review examines the clinical efficacy, pharmacological profile, and safety of the combination of dexmedetomidine and ketamine (Ketodex) in dental procedures. A comprehensive search was conducted in the PubMed, Scopus, Web of Science, and Google Scholar databases, including studies published between 2000 and 2025. Articles were selected that investigated the use of Ketodex in dentistry and compared it with other sedation protocols such as midazolam-fentanyl and propofol-ketamine (Ketofol). The combination of dexmedetomidine and ketamine demonstrated effective sedation, hemodynamic stability, and a low incidence of adverse events. The intranasal route stood out for its practicality and good tolerability, particularly in pediatric patients. Compared to traditional sedation protocols, Ketodex showed notable advantages, including enhanced respiratory safety and more favorable post-sedation recovery. Ketodex emerges as a promising alternative for sedation in outpatient dental settings, especially among vulnerable populations. However, multicenter studies with larger sample sizes and cost-effectiveness analyses are still needed to support its widespread implementation in clinical practice.